MODAL HEDGES USED ON MAIN CHARACTERS’ DIALOGUES IN KNIVES OUT MOVIE WRITTEN BY RIAN JOHNSON - Fadilah Fadilah; Fiza Asri Fauziah Habibah (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2021)
This is the study of the use of modal hedge category of hedging that is taken from the main characters’ dialogues in Knives Out movie. Knives Out tells the twists and turns of detective in solving a death case involving those closest to the victim. There are total 4 main characters who spoke with modal hedges contained in the dialogues. The method used is descriptive qualitative which describes the situation factually. There are 20 data found which are dialogues containing of modal hedge category of hedging. Researchers use the theory of the category of hedging by Yu which are modal hedges category. From the study, researcher found all kind of modal hedge category of hedging in the dialogues spoken by the main characters there 20 data found from modal hedges which spoke by all four main characters they are could, should, would, probably, maybe, may and might.